Fostering supportive community connections through mothers' groups and playgroups. (7th May 2014) - Strange, Cecily; Fisher, Colleen; Howat, Peter; Wood, Lisa
Abstract Aim The aim of this study was to explore the ways that mothers' groups and playgroups support families with children aged 0–5 years and foster community connectedness in newer residential communities in Perth, Western Australia. Background The transition to parenthood is a time of increased support need. Changing community demography has resulted in a loss of traditional support structures and an increased need for local community initiatives to support families with young children. Design A qualitative descriptive design was used for this initial phase of a mixed methods sequential exploratory study. Method Data were collected between December 2011–August 2012. Interviews and focus groups conducted with 39 mothers provided insights from 16 mothers' groups and 13 playgroups. In addition, interviews were undertaken with three child health nurses and four local government early childhood staff. Findings For the participants in this study, mothers' groups and playgroups provided opportunities to learn about parenting, to build a supportive network, to forge friendships and a connectedness to the local community. The families who relocated often experienced isolation until new groups and social networks were found. In general, where participation in mothers' groups and playgroups facilitated relationships with others from the local community, connectedness to that community was reported by participants to be enhanced. Conclusion Mothers' groups and playgroups provide important community development opportunities and appear to help reduce potential isolation for mothers with young children. The findings are of interest to nurses and other health professionals working with families with young children.